(3OjhGf GdYQbdI GdcdHjs - (3CHhGdfOG MSGf Hf fejQ Hf YLd GdcdHj, GdYQbdI,J (B567 (3g` s
(3ChdgG (B:s
(3bGd GdCOjH MSGf Hf fejQ, QMeg Gddg, GdcdHj aj GdfSjH hGdZRd(B: (3eG cdGe GdhTGI EdG cdGe hMeGe GdCQGc EdG MeGe s
(3BNQgG (B:s
(3hcja CNGa GdabQ Ch CMQe GdZfi hcahj ef GdCeUGQ eUQ hUQNO aCMhGd WdGY GdJfG WdGFY hdG RGd eMeh GdJMGjG eMeO s
(3GdfSNI HgG MhGTs
(3Ydi ghGeTgG CHjGJ TYQjI hJYdjbGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B191s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B517 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B156 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs